Design of NEMS Based Intraocular Pressure Sensing System. (2016) - Paulson, Greeshma Grace; Antony, Jobin K.
Abstract: Glaucoma is one of the leading causes of irreversible blindness. The change in intraocular pressure (IOP) inside the anterior chamber of the eye beyond its normal limit leads to this condition which initially affects the peripheral vision and if left untreated, results in permanent blindness. Early detection of elevation in IOP helps to slow down the disease progress. Thus a highly precise, cost effective, miniaturized pressure sensor is an important need for sensing the IOP. In the present work, the piezoresistivity of Single Walled Carbon Nano Tubes (SWCNT) is exploited to design a diaphragm based Nano-Electro-Mechanical Systems (NEMS) pressure sensor. Finite Element Method simulation is then performed to find the change in resistance ofthe piezoresistive material. This change in resistance results a change in output voltage corresponding to the pressure applied, which can be measured by an interfacing circuitry consisting of a low voltage amplifier andlow power-high speed Analog to Digital Converter (ADC). The resultant pressure sensor response is found to be highly linear and its sensitivity can be increased by changing diaphragm dimensions.